Three grades of subject-dependency in object perception. - Ivy, Spencer; Mroczko-Wąsowicz, Aleksandra (Synthese, 2025)
In this paper, we argue that a perceiver’s contributions to perception can substantially affect what objects are represented in perceptual experience. To capture the scalar nature of these perceiver-contingent contributions, we introduce three grades of subject-dependency in object perception. The first grade, “weak subject-dependency,” concerns attentional changes to perceptual content like, for instance, when a perceiver turns their head, plugs their ears, or primes their attention to a particular cue. The second grade, “moderate subject-dependency,” concerns changes in the contingent features of perceptual objects due to action-orientation, location, and agential interest. For instance, being to the right or left of an object will cause the object to have a corresponding locative feature, but that feature is non-essential to the object in question. Finally, the third grade, “strong subject-dependency,” concerns generating perceptual objects whose existence depends upon their perceivers’ sensory contributions to perception. For this final grade of subject-dependency the adaptive perceptual system shapes diverse representations of sensory information by contributing necessary features to perceptual objects. To exemplify this nonstandard form of object perception we offer evidence from the future-directed anticipation of perceptual experts, and from the feature binding of synesthetes. We conclude that strongly subject-dependent perceptual objects are more than mere material objects, but are rather a necessary combination of material objects with the contributions of a perceiving subject.